Analysis Of Consumer Preferences Towards The Decision To Purchase Isotonic Drinks Using The Conjoint Analysis Method - Yudit Oktaneldanora; Jerry Dwi Trijoyo Purnomo; Bustanul Arifin Noer (Information Technology and Science (ITScience), 2025)
Exercise is an important activity for maintaining physical and mental health. One of the factors supporting sports performance is the consumption of isotonic drinks, which help replace lost fluids and electrolytes. This study aims to analyze consumer preferences for isotonic drinks based on the attributes of sugar content, package size, price, and taste. The method used is conjoint analysis by distributing questionnaires to 185 respondents (athletes and sports fans) in Malang, Surabaya, and Kediri. The results showed that the most preferred combination of attributes is isotonic drinks with low sugar content, 500ml packaging, a price of Rp 3,000–Rp 4,000, and original flavor. The most influential attributes in purchasing decisions were taste (33%) and price (32%), followed by sugar content (19%) and package size (16%). Correlation analysis showed a strong relationship between actual and predicted preferences (Pearson's R = 0.787; Kendall's tau = 0.611), with a significance of <0.05, indicating the accuracy of the model. The managerial implications of this study are recommendations for isotonic drink manufacturers to focus product development on low-sugar variants with original flavors, affordable prices, and large packaging (500ml) to meet the preferences of sports consumers.